The Sources and Burial of Marine Organic Carbon in the Eastern China Marginal Seas - Cao, Yali; Bi, Rong; Wang, Xingchen; Chen, Xi; Hu, Jingwen; Wang, Yaoyao; Jiang, Yiqing; Zhang, Hailong; Xing, Lei; Zhao, Meixun (Frontiers in Marine Science, 2022)
The ecological functions and biogeochemical processes of continental marginal seas are important for the global carbon cycle. In the eastern China marginal seas (ECMS), phytoplankton productivity has increased significantly in recent decades, but the sources and burial processes of marine organic carbon (OC) remain under-studied. We analyzed the contents of marine lipid biomarkers (brassicasterol, dinosterol, and C37 alkenones) in surface suspended particles obtained from seven cruises between 2010 and 2015, and in surface sediments from eight cruises between 2006 and 2012 in the ECMS, to estimate marine OC sources and burial. The correlations between lipid biomarkers and environmental factors were quantified to reveal controlling factors. The study area was divided into four regions according to cluster analysis conducted based on sediment parameters. Our results showed that the concentrations of marine lipid biomarkers in surface water were high near large estuaries such as the Changjiang River Estuary and the Yellow River Estuary, but those in surface sediments were high in mud areas. Nutrient concentration was a key factor controlling phytoplankton biomass in surface water, with high nutrients enhancing the growth of diatoms and dinoflagellates, while haptophytes were more abundant in low-nutrient, high-salinity and cold environments. High marine OC contents calculated from total OC δ13C were mainly associated with fine sediments transported by coastal currents, and finally deposited in mud areas. The proto-burial efficiency of marine OC in the ECMS (7–19%) was markedly higher than the mean value in global marginal seas, with high values being located in the western coast of the ECMS. The proto-burial efficiency of total marine lipid biomarkers (6–24%) was quantified for the first time in our study, with overall values and spatial patterns similar to that of marine OC. A key parameter for marine OC and marine biomarker proto-burial efficiency was sediment grain size. The smaller the sediment grain size was, the better the marine OC and marine biomarker were retained. Our study provides an important basis to elucidate spatial distribution patterns and forcing mechanisms of marine OC in surface water (production process) and surface sediments (burial process), and to estimate carbon budgets in large marginal seas.